Generating Positive Words of Mouth in Healthcare Services - Noor, Sufiana (BISNIS, 2021)
Words of mouth is still an interesting issue to discuss. This research examine how service quality can influence trust to raise worth of mouth. Service quality divided into core services quality and peripheral service. Positive words of mouth measured by referencing intention. This study focus on how service quality effect both customer trust and words of mouth. The data were collected through a survey among patients in a private medical clinic in Kudus Regency. . The data were analyzed by using Structural Equation Model on AMOS 21. The findings in this study showed that core service quality influences trust and referencing intention directly also indirectly. Peripheral service quality has influences on trust but it has no direct effect on referencing intention. From this study, the medical clinic management can learn to improve service quality in order to increase positive words of mouth.